Combined effects of soret and dufour on MHD flow of a power-law fluid over flat plate in slip flow rigime - Reddy, Shashidar Borra; Rajasekhar, M.; Saritha, Kallu (Zielona Góra: Uniwersytet Zielonogórski)
A numerical model is developed to study the Soret and Dufour effects on MHD boundary layer flow of a power-law fluid over a flat plate with velocity, thermal and solutal slip boundary conditions. The governing equations for momentum, energy and mass are transformed to a set of non-linear coupled ordinary differential equations by using similarity transformations.
Keywords: power-law fluids; Soret number; Dufour number; slip boundary conditions; finite difference method; Prandtl number